Analisis Kualitas Website Rumah Sakit Umum Daerah Beriman Balikpapan Menggunakan Metode Webqual 4.0 dan Importance-Performance Analysis (IPA) - Natasia, Sri Rahayu; Insanittaqwa, Vika Fitratunanny; Al Hafid, Adil (LPPM ITK, 2023)
RSUD Beriman Balikpapan uses a website to introduce its facilities and services. However, there are several problems on the RSUD Beriman Balikpapan website, such as a lack of clarity in interactions and difficulty understanding the website, unclear directions, pages without content, less detailed information, and minimal interaction between users and the organization. Apart from that, an assessment of the quality of the website has never been carried out by the Beriman Balikpapan Regional Hospital. Based on these problems, it is necessary to analyze the quality of RSUD Beriman Balikpapan's website using the Webqual method and IPA (Importance-Performance Analysis) analysis. The assessment aims to increase the problem visibility to the stakeholders to improve the quality of the website. The instruments used in this research come from the Webqual 4.0 method, which includes three main dimensions: usability, information quality, and service interaction quality. The analysis technique applied is Importance-Performance Analysis (IPA), which will provide an overview of indicators that require improvement or need to be maintained based on the difference between perceived performance and user expectations. The results of the Webqual Index (WQI) calculation show an average value of 0.79, indicating that overall, the quality of the RSUD Beriman Balikpapan website is relatively good. Hypothesis testing shows significant differences between perceived performance and user expectations in all dimensions. The gap analysis produces an average gap value of -0.37. From the Importance-Performance Analysis, several indicators need to be considered for improvement. These indicators are related to the ease of navigation and use of the RSUD Beriman Balikpapan website, the provision of always up-to-date information, and services that align with the expectations promised on the RSUD Beriman Balikpapan website